Radiolabeling of Nanoparticles and Polymers for PET Imaging - Katharina Stockhofe; Johannes M. Postema; Hanno Schieferstein; Tobias L. Ross (MDPI AG, 2014)
Nanomedicine has become an emerging field in imaging and therapy of malignancies. Nanodimensional drug delivery systems have already been used in the clinic, as carriers for sensitive chemotherapeutics or highly toxic substances. In addition, those nanodimensional structures are further able to carry and deliver radionuclides. In the development process, non-invasive imaging by means of positron emission tomography (PET) represents an ideal tool for investigations of pharmacological profiles and to find the optimal nanodimensional architecture of the aimed-at drug delivery system. Furthermore, in a personalized therapy approach, molecular imaging modalities are essential for patient screening/selection and monitoring. Hence, labeling methods for potential drug delivery systems are an indispensable need to provide the radiolabeled analog. In this review, we describe and discuss various approaches and methods for the labeling of potential drug delivery systems using positron emitters.